Factor Influence Analysis of Corporate Value with Firm Size As Moderator Variable in Indonesia Stock Exchange - Jaja Suteja; Muhammad Rida Abas (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2018)
Corporate value is the representation of people’s judgement towards the company’s performance in general that usually correlated with stock price. Maximizing corporate value is the main goal of a company. By doing so, it will also improve the prosperity of shareholders. This present study aims to analyze the influence of capital structure, dividend policy, and profitability towards the corporate value by involving firm size as the moderator variable. The subjects are the companies of consumer goods industry sector that has been registered in Indonesia Stock Exchange from 201 until 2016. The result showed that capital structure, dividend policy, and profitability simultaneously have influence towards the corporate value with coefficient of determination (R2) 20.17%. Thus, moderately, firm size can negatively moderate the correlation between capital structures towards corporate value. However, it cannot moderate the correlation between ldividend policies towards the corporate value. Keywords: Corporate Value, Capital Structure, Dividend Policy, Profitability, Firm Size